2020
DOI: 10.1186/s12931-020-01522-w
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone rescues TGF-β1-mediated β2-adrenergic receptor dysfunction and attenuates phosphodiesterase 4D expression in human airway smooth muscle cells

Abstract: Glucocorticoids (GCs) and β2-adrenergic receptor (β2AR) agonists improve asthma outcomes in most patients. GCs also modulate gene expression in human airway smooth muscle (HASM), thereby attenuating airway inflammation and airway hyperresponsiveness that define asthma. Our previous studies showed that the pro-fibrotic cytokine, transforming growth factor- β1 (TGF-β1) increases phosphodiesterase 4D (PDE4D) expression that attenuates agonist-induced levels of intracellular cAMP. Decreased cAMP levels then dimini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Of note, this refers to TGF‐β levels in hospitalized patients before the onset of dexamethasone treatment. TGF‐β‐mediated pathology (e.g., airway remodeling and organ fibrosis) is known to be reduced by this treatment [14, 15]. Notably, serum levels of other cytokines elevated during the first 2 weeks of COVID‐19, that is, IFN‐α, IFN‐y, IL‐6, IL15, and IL‐18, did not forecast severe disease, further underscoring the predictive value of TGF‐β (Supporting Information Table S2 and Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Of note, this refers to TGF‐β levels in hospitalized patients before the onset of dexamethasone treatment. TGF‐β‐mediated pathology (e.g., airway remodeling and organ fibrosis) is known to be reduced by this treatment [14, 15]. Notably, serum levels of other cytokines elevated during the first 2 weeks of COVID‐19, that is, IFN‐α, IFN‐y, IL‐6, IL15, and IL‐18, did not forecast severe disease, further underscoring the predictive value of TGF‐β (Supporting Information Table S2 and Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, PDE4D deficiency in HFD mouse livers significantly reduced renal injury by decreasing TGF-β1 signal amplification in the kidney. Other studies have shown that the profibrotic cytokine TGF-β1 increases PDE4D expression [ 48 ]. Thus, PDE4D and TGF-β1 may positively regulate each other as renal fibrosis progresses and mediate liver-kidney crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…However, the apparent increase in D1DR fails to change D1DR signaling from full and partial agonists. Previous studies demonstrated that TGF-b1-mediated epithelial-mesenchymal transition of alveolar type II cells leads to an increase in the cAMP-specific phosphodiesterase 4 (PDE4) (Kolosionek et al, 2009); similarly, in tracheal smooth muscle, TGF-b1 reduces Ga s -mediated signaling (Chung et al, 2020). As PDE4 was not examined, it is unclear if the increase in receptor signaling is buffeted by an increase in PDE4.…”
mentioning
confidence: 99%